Ethics and society in Nigeria : identity, history, political theory - Wariboko, Nimi, 1962- (Rochester studies in African history and the diaspora, 2019)
Offers a radical political interpretation of history that generates fresh insights into the emancipatory potential of ordinary Nigerians and their precolonial cultural institutions.